Exegetical Evaluation Of Jesus’ Empathy in Luke 7:11-17: Implications for Baptist Churches in Sapele Delta State - Idoro, Okeoghene Emmanuel; Ottuh, Peter (dialektika kontemporer, 2025)
This study explores the role of Baptist churches in the Sapele metropolis in demonstrating empathy toward helpless widows, drawing insights from Luke 7:11-17. It examines the theological significance of empathy and its impact on socio-welfare and evangelism within the community. By highlighting the importance of compassionate support, the study underscores how empathy can help alleviate the socio-economic and financial challenges faced by widows. Additionally, it aims to inspire church leaders and individuals to extend care to vulnerable widows while raising awareness of the broader implications of such acts of kindness. The research employs exegetical and phenomenological methods to analyze Luke 7:11-17, providing a theological framework for fostering a culture of empathy in the church.